Maternal Mortality Rate before and after BPJS Health services Era : Angka Kematian Ibu sebelum dan sesudah Era BPJS - Hermie M. M. Tendean; Anastasia M. Lumentut; Maimun Ihsan (Indonesian Socety of Obstetrics and Gynecology, 2021)
Abstract Objective: To compare maternal death in RSUD dr. Aloei Saboe Gorontalo before BPJS (in 2011-2013) and after BPJS (2014-2016)Methods: Descriptive Retrospective. Data in this study obtained from the secondary data. This data obtained by the researcher from medical records in RSUD Prof. Dr. Aloei Saboe Gorontalo.Results: In this study, the number of delivery in hospitals Prof. Dr. Aloei Saboe before BPJS (2011-2013) of 7906 deliveries of live births after 7735 and health services BPJS (years 2014-2016) of 6493 deliveries of live births BPJS 6333. Maternal mortality before and after as many as 34 cases BPJS many as 42 cases, so we get the MMR before BPJS 4.39 ‰ and 6.63 ‰ after BPJS.Conclusion: There is a significant increase in maternal mortality rate in Prof. Dr. Aloei Saboe Gorontalo (p = 0.036), after BPJS maternal mortality (years 2014-2016) was 42 cases, compared with a prior health services BPJS (2011-2013) was 34 cases. This increase occurred because of a referral system BPJS make the decreasing number of births was in the hospital decreased, and hospitals Prof. Dr. Aloei Saboe a referral centre in Gorontalo province and surrounding areas.Keywords: death, BPJS, maternal, mortality. Abstrak Tujuan: Untuk membandingkan kematian maternal di RSUD Prof. Dr. Aloei Saboe sebelum BPJS (2011-2013) dan sesudah layanan kesehatan BPJS (2014-2016).Metode: Deskriptif Retrospektif. Jenis data yang digunakan dalam penelitian ini adalah data sekunder yang diperoleh dari rekam medik di RSUD Prof. Dr. Aloei Saboe Gorontalo.Hasil: Pada penelitian ini didapatkan jumlah persalinan di RSUD Prof. Dr. Aloei Saboe sebelum BPJS (2011-2013) sebanyak 7906 persalinan dengan kelahiran hidup 7735 dan sesudah layanan kesehatan BPJS (2014-2016) sebanyak 6493 persalinan dengan kelahiran hidup 6333. Kematian maternal sebelum BPJS sebanyak 34 kasus dan sesudah BPJS sebanyak 42 kasus, sehingga didapatkan AKI sebelum BPJS 4.39 ‰ dan sesudah BPJS 6.63 ‰.Kesimpulan: Ternyata terdapat peningkatan yang bermakna (p=0,036) kematian maternal sesudah BPJS (2014-2016) sebanyak 42 kasus, bila dibandingkan dengan sebelum layanan kesehatan BPJS (2011-2013) sebanyak 34 kasus. Peningkatan ini terjadi karena sistem rujukan BPJS membuat menurunnya jumlah persalinan yang ada dirumah sakit menurun, dan RSUD Prof. Dr. Aloei Saboe merupakan pusat rujukan di propinsi Gorontalo dan sekitarnya.Kata Kunci: BPJS, kematian, maternal,mortalitas